2007
DOI: 10.1002/ajmg.b.30481
|View full text |Cite
|
Sign up to set email alerts
|

Towards understanding the schizophrenia code: An expanded convergent functional genomics approach

Abstract: Identifying genes for schizophrenia through classical genetic approaches has proven arduous. Here, we present a comprehensive convergent analysis that translationally integrates brain gene expression data from a relevant pharmacogenomic mouse model (involving treatments with a psychomimetic agent - phencyclidine (PCP), and an anti-psychotic - clozapine), with human genetic linkage data and human postmortem brain data, as a Bayesian strategy of cross validating findings. Topping the list of candidate genes, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
129
1
1

Year Published

2008
2008
2009
2009

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 129 publications
(138 citation statements)
references
References 280 publications
7
129
1
1
Order By: Relevance
“…[1][2][3] In search of promising candidate genes, studies of gene expression in brain samples from patients with schizophrenia or various cellular and animal models have also been carried out. 4 Using such a functional convergent genomics approach, we investigated transcriptional responses in cultured human glial cells exposed to antipsychotic drugs. We found that some typical and atypical antipsychotics markedly upregulated several genes involved in the biosynthesis of cholesterol and fatty acids.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] In search of promising candidate genes, studies of gene expression in brain samples from patients with schizophrenia or various cellular and animal models have also been carried out. 4 Using such a functional convergent genomics approach, we investigated transcriptional responses in cultured human glial cells exposed to antipsychotic drugs. We found that some typical and atypical antipsychotics markedly upregulated several genes involved in the biosynthesis of cholesterol and fatty acids.…”
Section: Introductionmentioning
confidence: 99%
“…This approach has been applied, among others, to the study of bipolar disorder (Le-Niculescu et al, 2009b;Niculescu et al, 2000;Ogden et al, 2004) and schizophrenia (Le-Niculescu et al, 2007), as well as to the identification of blood biomarkers (Le-Niculescu et al, 2009a). Human data increase the relevance to the disorder (specificity), whereas animal model data increase the ability to identify the signal (sensitivity).…”
mentioning
confidence: 99%
“…In light of the fact that a large body of expression-based studies have shown significantly lower levels of PLP1 mRNA transcripts in animal models of schizophrenia or in brain tissue from deceased schizophrenic patients in comparison with healthy controls (Tkachev et al 2003;Aston et al 2004;Le-Niculescu et al 2007), our results suggest that the downregulation is not influenced by the predisposing common genetic variants within or in close vicinity to the PLP1 gene region.…”
Section: Discussionmentioning
confidence: 63%
“…An emerging body of work over the last 5 years has implicated myelin/glia related dysfunction in schizophrenia (Tkachev et al 2003;Aston et al 2004;Le-Niculescu et al 2007). Moreover, downregulation of at least some of the many abnormally expressed myelin-associated genes in schizophrenia might be influenced by a systematic mechanism such as methylation, as in case of SOX10 (Iwamoto et al 2005), or a transcriptional factor that can exert an effect on multiple myelin-associated genes such as QKI (Aberg et al 2006;Haroutunian et al 2006) rather than an SNP in the regulatory region of each abnormally expressed myelin-associated genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation